The Role of Digital Storytelling in the Improvement of Vocabulary Acquisition - Albishi, Ohoud Ali; Alqiawi, Dalal Abdullah (Journal of Curriculum and Teaching Methodology, 2022)
Digital storytelling DST is an effective combination of text, audio, and visual components. There are several techniques for teaching vocabulary: using illustrations and pictures, using expressions and gestures, and guessing from context. The combination of all these techniques is available via DST. Likewise, vocabulary is a vital skill in learning a foreign language. The acquisition of vocabulary is a critical aspect of success in using a foreign language. This research aims at investigating the role of digital storytelling in the improvement of vocabulary acquisition among students by presenting some related studies and highlighting the major results of those related studies. To achieve the research objectives, the researcher adopts the descriptive method. The results of this literature review show the effective use of digital storytelling improves vocabulary acquisition among students, enhances English language skills, supports the integration of technology, develops 21st century skills, and increases students’ motivation to learn a foreign language.
Keywords: digital storytelling; vocabulary; vocabulary acquisition